Prime Minister Decree No. 56 For The Year 2022 Determining The Terms Of Considering The Investment Project Strategic Or National In The Field Of Applying The Provision Of Article (20) Of The Investment Law Promulgated By Law No. 72 Of The Year 2017 = قرار مجلس الوزراء رقم 56 لسنة 2022 بتحديد شروط اعتبار المشروع الاستثمارى استراتيجياً أو قومياً فى مجال تطبيق حكم المادة (20) من قانون الاستثمار الصادر بالقانون رقم 72 لسنة 2017 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic